Chapter Teorie e modelli pedagogico-didattici per l'uso del video a 360° - Ranieri, Maria (Studi e saggi, 2022)
The chapter focuses on the learning theories (situated learning, experiential learning, transformative learning) that can allow one to highlight the pedagogical affordances of the 360° video, paying a particular attention to the Higher Education context and also offering an overview of possible educational scenarios based on the use of 360° video. In addition, it examines the main benefits and barriers of 360° video in the educational field.